Contemporary Muslim World towards Globalization and Mass Communication: Analytical Study - Muhammad Umar Riaz Abbasi; Dr. Syed Abdul Ghaffar Bukhari (Al-Qamar, 2020)
Since, the concept of globalization is defined as cross-cultural integration, which ultimately results in technological advancement, increase in commercialization, and increase in the foreign direct investment. The problem related to the concept of globalization and mass communication in the Islamic perspective is the hindrances in the education of Islam via the execution of conventional mass communication. Further, sustainability in the ideology of Islam is a big issue at the global level because some Islamic dominant countries have different perspectives related to the ideology of Islam. This research study incorporates the qualitative method that helps in analyzing the concept of globalization and mass communication, in the light of the Islamic perspectives. The research mainly gathers the qualitative data from the secondary sources. In the data analysis section, it strives to learn about the concept of globalization and mass communication by initiating a content analysis. This research, in particular, opts for the primary methods where data is gathered from the previous research study, case study, and news article. The data would be pertaining to the concept of globalization and mass communication in accordance with the Islam perspective. The data analysis would mainly be analyzing the literature obtained from the past research, news article and website. Mass communication comes under the umbrella of the information and communication systems and it is defined as the communication of information from an individual, large or small group of people, or a small corporation to a large group of assorted and mysterious people. Mass communication is useful for the people in the communication of Islam to guide the people about Islam and spread Islamic education to the people.